Use of agroindustrial residue in the production of angico vermelho seedlings - Lobo, Thomaz Figueiredo [UNESP]; Olher, Izabella; Siqueira, Marcos Vinícius Bohrer Monteiro; Oliveira, Fernando Carvalho (Fronteiras: Journal of Social, Technological and Environmental Science, 2021)
Disorganized urban growth has caused numerous problems to the environment due to large scale waste production. The problem of the effluents of the cities indicate that the waste management is necessary, showing one of the main challenges to the final destination. These residues can be used in the production of substrates in nursery seedlings. The objective of this work was to evaluate the composted sewage sludge (LEC) and commercial substrate (SC), through different mixtures, in the production of angico vemelho seedlings. Five treatments (T) were constituted, T1 (100% LEC); T2 (75% LEC and 25% SC); T3 (50% LEC and 50% SC); T4 (25% LEC and 75% SC) and T5 (100% SC). The biometric parameters analyzed were height, neck diameter, total dry mass, Dickson Quality Index and final levels of nutrients contained in the substrate. T3 presented the best values in most of the evaluated parameters. These results present a promising alternative for the use of LEC in the composition of substrates for the seedlings forest species production.
Aproveitamento de Resíduo Agroindustrial na Produção de Mudas de Angico Vermelho
Keywords: Composted sewage sludge; Native seedlings Parapiptadenia pterosperma; Plant nutrition